2017
DOI: 10.1681/asn.2016091043
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylation of IgA1 Is Associated with Common Variation in C1GALT1

Abstract: IgA nephropathy (IgAN), an important cause of kidney failure, is characterized by glomerular IgA deposition and is associated with changes in O-glycosylation of the IgA1 molecule. Here, we sought to identify genetic factors contributing to levels of galactose-deficient IgA1 (Gd-IgA1) in Caucasian and Chinese populations.Gd-IgA1 levels were elevated in IgAN patients compared with ethnically matched healthy subjects and correlated with evidence of disease progression. Caucasian IgAN patients exhibited significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 48 publications
4
79
0
Order By: Relevance
“…Recent GWAS findings showed an association of IgAN with SNPs for critical glycosyltransferase and chaperone genes, C1GALT1 and COSMC. These data were validated with in vitro studies that revealed that 2 genome-wide significant loci, on chromosomes 7p21.3 and Xq24, influence Gd-IgA1 production [15,16]. Furthermore, environmental factors, such as mucosal infections, may further accentuate the aberrant O-glycosylation of IgA1.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Recent GWAS findings showed an association of IgAN with SNPs for critical glycosyltransferase and chaperone genes, C1GALT1 and COSMC. These data were validated with in vitro studies that revealed that 2 genome-wide significant loci, on chromosomes 7p21.3 and Xq24, influence Gd-IgA1 production [15,16]. Furthermore, environmental factors, such as mucosal infections, may further accentuate the aberrant O-glycosylation of IgA1.…”
Section: Discussionmentioning
confidence: 65%
“…These findings together suggested that elevated production of Gd-IgA1 in patients with IgAN was due to an abnormal biosynthesis in IgA1-secreting cells rather than galactose removal/degradation. This conclusion was further supported by 2 genome-wide association studies (GWAS) that implicated variants of C1GALT1 and COSMC in Gd-IgA1 serum levels [15,16].…”
Section: Introductionmentioning
confidence: 76%
“…In the same study Gale et al also showed for the first time a striking disparity in the levels of poorly O-galactosylated IgA1 between Caucasian and Chinese subjects, both healthy and IgAN cases. 101 This study raises important questions given that IgAN is more prevalent in Chinese populations, associated with worse outcomes and more inflammatory lesions in the kidney while levels of circulating poorly O-galactosylated IgA1 are lower than that seen in Caucasians-both IgAN and healthy subjects, and the frequency of the C1GALT1 risk haplotype risk is 10 times less frequently found in Chinese people compared to Europeans. In light of these observations, the pathogenic importance of changes in IgA1 O-galactosylation in different ethnic populations must be re-evaluated.…”
Section: Differences In Pathogenic Pathways In Igan In Different Ethnmentioning
confidence: 90%
“…In a recent quantitative trait GWAS multiple single nucleotide polymorphisms (SNP) were identified in the non‐coding region of the C1GALT1 gene to be associated with the extent of serum IgA1 O ‐galactosylation in IgAN, healthy subjects, membranous nephropathy in Caucasian and Chinese cohorts. In the same study Gale et al also showed for the first time a striking disparity in the levels of poorly O‐ galactosylated IgA1 between Caucasian and Chinese subjects, both healthy and IgAN cases . This study raises important questions given that IgAN is more prevalent in Chinese populations, associated with worse outcomes and more inflammatory lesions in the kidney while levels of circulating poorly O ‐galactosylated IgA1 are lower than that seen in Caucasians‐both IgAN and healthy subjects, and the frequency of the C1GALT1 risk haplotype risk is 10 times less frequently found in Chinese people compared to Europeans.…”
Section: Differences In Pathogenic Pathways In Igan In Different Ethnmentioning
confidence: 99%
“…Recent genome-wide association analyses confirmed C1GalT1 gene as one of critical genetic factors playing role in the Gd-IgA1 formation [10, 11]. Other recent studies suggested involvement of polymorphism in immune signalling molecules like IFN-γ and IL-10 [12, 13].…”
Section: Introductionmentioning
confidence: 99%